Metal catalyzed defunctionalization reactions. Issue 1 (13th November 2015) - Modak, Atanu; Maiti, Debabrata
Abstract : The chronological development of metal assisted defunctionalization reactions is discussed from the stoichiometric to the catalytic stage with their application in synthetic organic chemistry. Abstract : Defunctionalization has a direct impact on the synthesis of value added products ( e.g. biomass degradation). In synthetic chemistry it enables the functional group to act as a transient directing group. In this mini review, we have described the chronological development of metal assisted defunctionalization reactions from the stoichiometric to the catalytic stage with their application in synthetic organic chemistry. The proposed catalytic cycles of the transformations have been described to make this review comprehensible.